Individualization of independent work in the professional training of future teachers: An experimental study - Y. Sylenko (Mukachevo State University, 2024)
The individualisation of independent work in the professional training of future teachers contributes to the stable achievement of results in professional and pedagogical training, as it takes into account the needs, motivation, and capabilities of the student. One of the leading technologies of innovative education is tutoring, which ensures an open educational environment in a higher education institution. The article outlines the results of an experimental study of the state of individualisation of independent work in the professional training of future university teachers on the basis of comprehensive, competence-based, systemic and activity-based approaches. The experiment was conducted in the form of a questionnaire among 54 respondents - master students majoring in "011 - Educational, Pedagogical Sciences" of the Mykhailo Drahomanov Ukrainian State University in order to find out their attitude to the current individualisation of independent work and the introduction of tutoring technology. The respondents were offered a Google Forms questionnaire "The current state of individualisation of students' independent work in higher education institutions", which consisted of 10 questions with possible answers. The results of the experiment showed that modern higher education institutions do not provide adequate conditions for the development of important skills and qualities in students, such as independence, the ability for self-education, self-development, and self-knowledge. It is established that the majority of master's students express their dissatisfaction with the organisation of individualised independent work in higher education institutions, which is due to insufficient attention to their interests, needs, and motives. It is proposed to introduce an integrated form of professional and pedagogical training of future teachers - tutoring technology as an important mechanism for innovating education, which can ensure the openness of the educational and scientific environment. The essence of the educational process under the guidance of a tutor, when a student acts as a tutor on the basis of subject-subject partnership interaction, is revealed. The results of the confirmatory experiment make it possible to further study the conceptual foundations of tutoring as a leading technology for individualising the educational and scientific process. The developed experimental study on the current state of individualisation of independent work in higher education institutions can be implemented at all levels of training of future pedagogical specialists